PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) BERBASIS LOCAL BASED CURRICULUM TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DI SMAN 1 PARIAMAN - Salma; Wilis, Ratna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Group Investigation (GI) learning model based on the Local Based Curriculum approach in Geography learning at SMAN 1 Pariaman, and to examine its effect on students' critical thinking ability. A quantitative approach was used with a quasi-experimental method and a Non-Equivalent Control Group Design. The sample consisted of class XI F6 as the experimental group and class XI F7 as the control group, selected through purposive sampling. Data were collected through pretest and posttest instruments and analyzed using normality tests, homogeneity tests, the Independent Sample t-Test, and N-Gain calculation. The results show that the GI model based on the Local Based Curriculum was implemented in accordance with its syntax, namely identifying topics and forming groups, planning the investigation, carrying out the investigation, preparing and presenting the report, and conducting evaluation and reflection. The model also had a significant effect on students' critical thinking ability, as shown by the average N-Gain score of the experimental class (0.7121, high category) which was higher than that of the control class (0.5121, moderate category). The Independent Sample t-Test result showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, meaning H₀ was rejected and H₁ was accepted.